2016
DOI: 10.1021/acsami.6b07338
|View full text |Cite
|
Sign up to set email alerts
|

Nanoceria-Mediated Drug Delivery for Targeted Photodynamic Therapy on Drug-Resistant Breast Cancer

Abstract: Photodynamic therapy (PDT) has shown great potential for overcoming drug-resistant cancers. Here, we report a multifunctional drug delivery system based on chlorin e6 (Ce6)/folic acid (FA)-loaded branched polyethylenimine-PEGylation ceria nanoparticles (PPCNPs-Ce6/FA), which was developed for targeted PDT to overcome drug-resistant breast cancers. Nanocarrier delivery and FA targeting significantly promoted the cellular uptake of photosensitizers (PSs), followed by their accumulation in lysosomes. PPCNPs-Ce6/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 68 publications
3
92
1
Order By: Relevance
“…The nanocarrier delivery and FA targeting promoted cellular uptake of photosensitizers (PSs), which are selectively accumulated in lysosomes and could be triggered to produce ROS by a 660 nm laser, and then lead to the decreased expression of P-glycoprotein (P-gp) drug-efflux pumps. This phenomenon promoted the chemotherapeutic efficacy of DOX and enhanced phototoxicity in drug-resistant human breast cancer cells [15]. It was found that induction of apoptotic/autophagic or oncosis processes completely depended on the dose of lysosomal-PDT (Figure 8).…”
Section: Targeted Drug and Photodynamic Therapymentioning
confidence: 96%
See 3 more Smart Citations
“…The nanocarrier delivery and FA targeting promoted cellular uptake of photosensitizers (PSs), which are selectively accumulated in lysosomes and could be triggered to produce ROS by a 660 nm laser, and then lead to the decreased expression of P-glycoprotein (P-gp) drug-efflux pumps. This phenomenon promoted the chemotherapeutic efficacy of DOX and enhanced phototoxicity in drug-resistant human breast cancer cells [15]. It was found that induction of apoptotic/autophagic or oncosis processes completely depended on the dose of lysosomal-PDT (Figure 8).…”
Section: Targeted Drug and Photodynamic Therapymentioning
confidence: 96%
“…At present, pathogenic mechanism of T2DM and control method became a hot topic in medical research. Different sized nanoceria (15,25,30, and 45 nm) was prepared by Park and coworkers [38] via supercritical synthesis method. Oxidative stress was induced by different concentration nanoceria (5, 10, 20, and 40 g/mL) in cultured human lung epithelial cells (BEAS-2B).…”
Section: Signal Transduction For Pathogenic Mechanism Of Typementioning
confidence: 99%
See 2 more Smart Citations
“…For example, co-loading of hematoporphyrin and doxorubicin in nanoparticles can increase the sensitivity of chemotherapeutic drugs by approximately 12-fold. 102 However, several studies have demonstrated hypoxia is responsible for chemoresistance. 101 Li et al demonstrated that PDT mediated by PSloaded nanocarriers can reverse the drug resistance of breast cancer by decreasing the expression of p-gp and increasing the concentration of DOX in tumor cells.…”
Section: Recent Advance Of Nanoparticle-based Pdtmentioning
confidence: 99%